Analisis Sistem Dan Pengembangan Sistem Informasi Penerimaan Siswa Baru Tingkat SMA Berbasis Web Online Dengan Metode Kualitatif - Meily Fristia Sinaga; Sri Pita Locha Surbakti; Tegar Meskur Fetaroma Zalukhu; M. Diarmansyah Batubara (Jurnal Sains dan Teknologi, 2021)
This research was conducted to analyze and develop an online web-based application "System Analysis and Development of New Student Admission Information Systems for High School Level Online Web-Based With Qualitative Methods" which is able to manage the implementation of New Student Admissions specifically at SMA Free Methodist 2 Medan, namely registration, selection, and announcements. Data collection techniques in this study were observation and interviews. The method used is a qualitative method. Testing is done by means of black-box testing and the analysis technique used in this research is descriptive analysis. The web uses the PHP and SQL programming languages. The results of the research on System Analysis and Development of Online Web-Based New Student Admissions Information Systems with this qualitative method are able to manage New Student Admissions from 4 paths, namely zoning, achievement, teacher's children or moving, affirmations. So that it covers all circles of society which private schools generally do not do.